2022
DOI: 10.1108/jeas-09-2021-0190
|View full text |Cite
|
Sign up to set email alerts
|

Volatility spillovers among G7, E7 stock markets and cryptocurrencies

Abstract: PurposeThe existence of long memory and persistent volatility characteristics of cryptocurrencies justifies the investigation of return and volatility/shock spillovers between traditional financial market asset classes and cryptocurrencies. The purpose of this paper is to investigate the dynamic relationship between the cryptocurrencies, namely Bitcoin and Ethereum, and stock market indices of G7 and E7 countries to analyze the return and volatility spillover patterns among these markets by means of multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Only a few of these studies considered volatility spillover and shock transmission effects, and there is a clear need for more studies that investigate the volatility spillovers between cryptocurrencies and financial assets (Bouri et al, 2018). On the other hand, the studies that investigated spillovers between these financial assets and cryptocurrencies concluded that there are bidirectional volatility spillovers between Bitcoin and S&P 500 (Ghorbel and Jeribi, 2021), bidirectional volatility spillovers between Bitcoin and MSCI emerging markets (Bouri et al, 2018), unidirectional spillovers between Bitcoin and FTSE 100 (Aydoğan et al, 2022) and unidirectional spillovers between Bitcoin and Nikkei 225 (Van de Klashorst, 2018). When cryptocurrencies and stock markets are compared, the presence of return and shock spillovers suggest the movement of investors across markets; searching for alternative assets or exiting current stocks where Bitcoin is often perceived as an alternative asset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Only a few of these studies considered volatility spillover and shock transmission effects, and there is a clear need for more studies that investigate the volatility spillovers between cryptocurrencies and financial assets (Bouri et al, 2018). On the other hand, the studies that investigated spillovers between these financial assets and cryptocurrencies concluded that there are bidirectional volatility spillovers between Bitcoin and S&P 500 (Ghorbel and Jeribi, 2021), bidirectional volatility spillovers between Bitcoin and MSCI emerging markets (Bouri et al, 2018), unidirectional spillovers between Bitcoin and FTSE 100 (Aydoğan et al, 2022) and unidirectional spillovers between Bitcoin and Nikkei 225 (Van de Klashorst, 2018). When cryptocurrencies and stock markets are compared, the presence of return and shock spillovers suggest the movement of investors across markets; searching for alternative assets or exiting current stocks where Bitcoin is often perceived as an alternative asset.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, based on the identified connectedness among the financial markets globally, recent researchers conducted a study on the dynamic linkages between macroeconomic variables and stock markets across the globe. The studies use advanced econometric techniques such as VAR-GARCH-BEKK, GVAR, GARCH-BEKK, BEKK-MGARCH, and others to identify dynamic linkages such as spillover effect, contagion, shock transmission, and so on [2,16,21]. But there is no superior model due to varied market conditions [17].…”
Section: Literature Reviewmentioning
confidence: 99%
“…A few studies are also being conducted on identifying the linkages between the crypto-currency market and the stock market [2,16,32]. The studies suggested a link between stock market returns and cryptocurrency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…As per the data from coinmarketcap.com, as of August 2022, a total of 20,679 cryptocurrencies across 513 exchanges have surpassed a market capitalization of over $1,023bn. Despite the inherent risk and uncertainty associated with the cryptocurrency market, it is starting to draw interest from investors as a new financial investment tool (Aydo gan et al, 2022). Because of several factors, including the potential high returns, the absence of onerous government rules and the decentralized nature.…”
Section: Introductionmentioning
confidence: 99%